Pengaruh E-Trade Dan Psychographic Terhadap Perilaku Investor PT Royal Assetindo Batam - Muhammat Rasid Ridho (Universitas Putera Batam, 2014)
Trade on stock exchanges, is now beginning to change slowly toward highly sophisticated. As the capital market management authorities in Batam, Batam PT Royal Assetindo still experiencing no little trouble in giving access to the capital markets for the whole society. So the writer is interested in conducting research on the effects of e -trade and the behavior of investors psychographic PT Royal Assetindo Batam. This study aims to determine how much influence the e -trade and psychographic behavior of investors towards Batam PT Royal Assetindo partially. And to know how big the influence of e -trade and psychographic behavior of investors towards Batam PT Royal Assetindo simultaneously. Authors conducted a study using two causal research design is the design or verification . With the number of respondents 96 investors from PT Royal Assetindo Batam. The findings of this study E -trade and psychographic positive and significant impact on investor behavior Batam PT Royal Assetindo either partially or simultaneously.